2020
DOI: 10.1038/s41598-020-75345-6
|View full text |Cite
|
Sign up to set email alerts
|

High gene flow maintains genetic diversity following selection for high EPSPS copy number in the weed kochia (Amaranthaceae)

Abstract: Kochia, a major weed species, has evolved resistance to four herbicide modes of action. Herbicide resistance appears to spread quickly, which could result in diminished standing genetic variation, reducing the ability of populations to adapt further. Here we used double digest restriction enzyme associated sequencing to determine the level of gene flow among kochia populations and whether selection for glyphosate resistance reduces genetic variation. Canadian Prairie populations show little to no genetic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…The mating system, that is, functional androdioecy, and the contrasting levels of gene flow might explain the high genetic diversity of this narrowly distributed species in some way [44,45]. The presence of null and dropout alleles will lead to a high deviation between Ho and He, and a high frequency of null alleles will cause the deviation from HWE in all loci [42,46].…”
Section: Genetic Diversity Of Osmanthus Serrulatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The mating system, that is, functional androdioecy, and the contrasting levels of gene flow might explain the high genetic diversity of this narrowly distributed species in some way [44,45]. The presence of null and dropout alleles will lead to a high deviation between Ho and He, and a high frequency of null alleles will cause the deviation from HWE in all loci [42,46].…”
Section: Genetic Diversity Of Osmanthus Serrulatusmentioning
confidence: 99%
“…In general, the genetic diversity of plants is positively correlated to the geographical range and population size, and the population decline leads to a loss of genetic diversity [43,45,48]. Endangered, endemic and narrowly distributed species usually have low genetic diversity, but many studies have shown that even endangered plants can have a moderate or high level of genetic diversity, such as Michelia coriacea Hung T. Chang & B. L. Chen (He = 0.505) [49], Rhododendron jingangshanicum P. C. Tam (He = 0.642) [50], Houpoea officinalis (Rehder & E. H. Wilson) N. H. Xia & C. Y. Wu (He = 0.600, I = 1.158) [51], Populus wulianensis S. B. Liang & X. W. Li (He = 0.611, I = 1.114, PPL = 98.6%) [26], Pteroceltis tatarinowii Maxim.…”
Section: Genetic Diversity Of Osmanthus Serrulatusmentioning
confidence: 99%
“…The plants are heat, drought, and saline tolerant (Friesen et al 2009). Protogynous flowering aids in cross-pollination resulting in the transfer of herbicide resistance traits, and populations maintain high genetic diversity within and among fields (Beckie et al 2016;Martin et al 2020). In the fall, the stem abscises resulting in a tumbleweed that can disperse seeds among multiple fields within a single year.…”
Section: Introductionmentioning
confidence: 99%
“…gene duplication, gene flow, herbicide resistance, independent evolution, mobile genetic elements, population genetics the semi-arid arable lands of the western USA and Canada (Friesen et al, 2009). Kochia populations from North America exhibit high levels of genetic diversity but a lack of strong population structure (Kumar et al, 2019;Martin et al, 2020;Mengistu & Messersmith, 2002), probably due to several reproductive traits that promote cross-pollination and long-range dispersal of pollen and seed (Beckie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%